Exploration of Sn70Li30 alloy as possible material for flowing liquid metal plasma facing components. (December 2020) - de Castro, A.; Moynihan, C.; Stemmley, S.; Szott, M.; Andruczyk, D.; Ruzic, D.N.
Highlights: First wetting data for Sn70 Li30 alloy are reported on 316 SS, Mo and W substrates. Wetting temperatures of 360 °C, 390 °C and 405 °C were measured respectively. Alloy contamination/passivation worsened wettability with Δ T~130 °C in worst cases. First depth profile characterization of the tin-lithium alloy by SIMS-ToF was carried out. Mixing boundaries between alloy and substrates studied by SEM/EDS and 3D microscopy. Lithium and tin induced corrosion found on 316 SS exposed at T < 550 °C during t ≤ 3 h. Molybdenum and tungsten presented good compatibility after equivalent interaction. Abstract: As an advanced alternative to solid materials, Liquid Metals (LM) may offer more resilient and feasible Plasma Facing Components (PFCs). Particularly, regarding the unavoidable material erosion/degradation produced by particle/heat fluxes in future fusion devices where much longer duty cycles are expected. Furthermore, configurations that propose a flowing LM surface can add the advantage of a continuously fresh and clean layer facing the plasma. Although lithium is the most widely tested option, tin-lithium (SnLi) alloys have been proposed to attempt to combine the positive characteristics of both pure elements and ameliorate the specific issues of lithium. In this work, the potential use of Sn70 Li30 alloy in such flowing concepts has been explored by addressing several preliminary and mandatory aspects for its utilization. Key issues such as wettability and compatibility of the alloy with relevant substrates have been studied in a multidisciplinary approach. The data obtained from deposited liquid tin-lithium droplets indicates approximate wetting temperatures of 360 °C, 390 °C and 405 °C for the fresh alloy on 316 stainless steel, molybdenum, and tungsten, respectively. However, the alloy contamination appeared to strongly affect the wetting characteristics of materials, increasing their wetting temperature by ~130 °C in the worst observed cases. Interestingly, in some instances, the instability of the liquid alloy surface was observed in the form of sudden gaseous ejection. The deposited droplets were posteriorly characterized in terms of absolute composition and depth profile by Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP-OES) and Secondary Ion Mass Spectrometry (SIMS-ToF). Additionally, the nature and composition of the boundaries between the substrates and alloy microparticles was investigated by Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray Spectroscopy (EDS), and 3D Laser microscopy. The overall results of this post-mortem characterization revealed that first signs of corrosion induced by both alloy elements (lithium-chromium association and iron-tin intermetallic mixing) were present on 316 stainless steel after short exposures (≤3 h) at temperatures lower than 550 °C. Conversely, molybdenum and tungsten showed good compatibility with the alloy in equivalent conditions. The global implications of these results are finally addressed, focusing on the future perspectives and the more viable scenarios for the eventual utilization of these alloys in flowing liquid metal configurations.